Forecast of the structure of heat supply of Ukraine for the period till 2040 - Bilodid V.D. (General Energy Institute of the National Academy of Sciences of Ukraine, 2016)
Based on the analysis of the state of heat supply and hypothetical variant of the forecast of economic development of Ukraine, we substantiate the grounds for the reasonable strategy of the development of Ukrainian heating systems for the period till 2040. We propose the rational structure of heat-generating capacities of the country by two scenarios: excluding the occupied territories (AR of Crimea and certain parts of Donetsk and Lugansk regions) and for the whole Ukraine. The development of this branch is proposed to be carried out mainly on the basis of wide using heatpump technologies and alternative types of fuel, which will lead to the reduction of natural gas consumption and heat production by boiler houses. According to scenario 1 (in the case of return of the occupied territories to Ukraine), it is estimated that the volume of heat energy generation in 2040 will reach 439.1 million Gcal. According to scenario 2 (in the case of non-return of the occupied territories to Ukraine), the estimated volume in 2040 will be by 80 million Gcal less.